2007
DOI: 10.1158/0008-5472.can-07-0970
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Progression of Pancreatic Intraepithelial Neoplasia in a Conditional KrasG12D Mouse Model by a Selective Cyclooxygenase-2 Inhibitor

Abstract: Pancreatic ductal adenocarcinomas are thought to arise from noninvasive, intraductal precursor lesions called pancreatic intraepithelial neoplasias (PanIN). The study of PanINs holds great promise for the identification of early detection markers and effective cancer-preventing strategies. Cyclooxygenase-2 (COX-2) represents an intriguing target for therapeutic and preventive approaches in various human malignancies. The aim of the present study was to evaluate the efficacy of a selective COX-2 inhibitor to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 17 publications
6
81
1
Order By: Relevance
“…Even though tumor-derived PGE2 was not evaluated in that study, a number of reports have demonstrated the overexpression of COX-2 or PGE2, and their tumor-promoting roles in spontaneous pancreatic cancer model (44), or human pancreatic cancer tissues (45,46). Thus, it is likely that GM-CSF, PGE2, as well as other tumor-derived inflammatory mediators, collaborate in promoting the induction of MDSCs in cancers.…”
Section: Discussionmentioning
confidence: 96%
“…Even though tumor-derived PGE2 was not evaluated in that study, a number of reports have demonstrated the overexpression of COX-2 or PGE2, and their tumor-promoting roles in spontaneous pancreatic cancer model (44), or human pancreatic cancer tissues (45,46). Thus, it is likely that GM-CSF, PGE2, as well as other tumor-derived inflammatory mediators, collaborate in promoting the induction of MDSCs in cancers.…”
Section: Discussionmentioning
confidence: 96%
“…Taken together, these data support that activation of NF-κB and its target gene Cox-2 mediate amplification of Ras signaling when oncogenic Ras is present (Figure 8). Further support for a role for Cox-2 in Ras-mediated pathologies comes from previous studies that indicated high levels of Cox-2 expression in human PanIN lesions (39) and reported that Cox-2 inhibitors reduced the development of pancreatic cancer in oncogenic Ras-based mouse models (40). The current study indicates that targeting NF-κB and Cox-2 pathways would be likely to reduce Ras activity in cells that bear this mutation and therefore may be clinically useful to prevent oncogenic Ras-induced diseases.…”
Section: Figurementioning
confidence: 94%
“…Previous studies have shown that inhibiting the COX-2 pathway suppresses the development of many cancers including pancreatic cancer (32). Also, COX-2 gene expression and its primary metabolite prostaglandin E2 (PGE 2 ) were highly expressed in 90% of pancreatic tumors (7).…”
Section: Discussionmentioning
confidence: 99%